A Genlis education and Enlightenment values - Yim, Denise, 1947- author.
1 online resource.
Keywords: "Offering a unique approach to the study of late eighteenth-century/early nineteenth-century education, this book explores the life and motivations of a strong-minded, self-educated and enlightened English gentlewoman, Mrs Margaret Chinnery, who put Madame de Genlis's educational ideas into practice with marked success. Beginning with a brief outline of Margaret's own childhood and her adolescent efforts to educate herself, drawing largely on readings recommended by Genlis, the book continues through to her marriage, her children's early and adolescent education, and ends with the benefits that the children gained in adulthood from their education. This book is not limited to a biography, as each section on the daily business of education is interspersed with a discussion and comparison of contemporary education authors and other writers, the values they espoused, which ones Margaret followed and why. It also draws on valuable surviving Chinnery documents which trace the Chinnery children's education, Margaret's correspondence with Genlis and a comprehensive catalogue of the Chinnery library. The book offers a unique opportunity to follow a real family from cradle to grave, and provides an intriguing illustration, at an individual level, of female-crafted education set against Enlightenment values. This book will be of great interest to postgraduate students and scholars researching the history and philosophy of education as well as women in the Enlightenment"--